2020
DOI: 10.3390/ijms21041376
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Approaches Against Brain Diseases Associated with Cytomegalovirus Infections

Abstract: Cytomegalovirus (CMV) is one of the major human health threats worldwide, especially for immunologically comprised patients. CMV may cause opportunistic infections, congenital infections, and brain diseases (e.g., mental retardation and glioblastoma). The etiology of brain diseases associated with human CMV (HCMV) infections is usually complex and it is particularly difficult to treat because HCMV has a life-long infection in its hosts, high mutation rate, and latent infections. Moreover, it is almost impossib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…The HCMV is a probable pathogen of brain diseases including glioblastoma (GBM). Certain malignant GBM expresses HCMV-related proteins, including the immediate early gene-1 product and the lower matrix phosphoprotein 65 (pp65) expressed by the unique long 83 (UL83) gene, indicating that HCMV may have played a role in the generation of GBM [32][33][34][35]. A certain animal study has revealed that CMV can induce GBM formation in vitro and in xenograft models and HCMV can also be detected in GBM isolated from patients, suggesting that HCMV may drive tumorigenesis or be reactivated in tumors [35].…”
Section: Glioblastoma (Gbm) For Adultsmentioning
confidence: 99%
“…The HCMV is a probable pathogen of brain diseases including glioblastoma (GBM). Certain malignant GBM expresses HCMV-related proteins, including the immediate early gene-1 product and the lower matrix phosphoprotein 65 (pp65) expressed by the unique long 83 (UL83) gene, indicating that HCMV may have played a role in the generation of GBM [32][33][34][35]. A certain animal study has revealed that CMV can induce GBM formation in vitro and in xenograft models and HCMV can also be detected in GBM isolated from patients, suggesting that HCMV may drive tumorigenesis or be reactivated in tumors [35].…”
Section: Glioblastoma (Gbm) For Adultsmentioning
confidence: 99%